Pengaruh Return on Asset, Return on Equity, dan Net Profit Margin terhadap pertumbuhan laba pada perusahaan sub sektor farmasi yang terdaftar di Bursa Efek Indonesia tahun 2016-2020 - Fathimah, Nur Aini; Hertina, Dede (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Profit growth is the difference between the profit generated from a period and the profit generated in the previous period. The purpose of this study is to obtain empirical evidence regarding the effect of Return On Assets (ROA), Return On Equity (ROE), and Net Profit Margin (NPM) on Profit Growth. The population of this study are pharmaceutical companies listed on the IDX. The sample in this study were 6 companies selected by purposive sampling method. The analytical method used is the panel data regression method. Based on the hypothesis, the results of the study show that Return on Assets has no positive effect on Profit Growth, Return On Equity has a positive effect on Profit Growth, and Net Profit Margin has no negative effect on Profit Growth.